Identification, cloning and characterization of a novel Gossypium hirsutum L. GhMYBantiV transcription factor in response to biotic and abiotic stresses - Fei, Li; Xiaoyan, Chen; Xiaohong, He; Ming, Tang; Kun, Hong; Zhengting, Yang; Yin, Yi; Zhanji, Liu; Mingchuan, Fu (The Indian Journal of Genetics and Plant Breeding, 2017)
Verticillium wilt is an important worldwide limiting factorfor cotton production. Improving cotton varieties’ diseaseresistance, is of great strategic and practical importanceto promote world cotton production and to improve cottonfibre quality. Taking advantage of the Gossypium raimondiigenome sequence, we cloned a new MYB transcriptionfactor GhMYBantiV (GenBank accession number:KM0407832) from upland cotton variety Lumianyan 32.Characteristic analysis indicates that GhMYBantiV is a MYBtranscription factor, since it localises in the nucleus, andshows the transcription factor activity. GhMYBantiVexpression is greatly enhanced by Verticillium wilt fungusinfection and salt treatment. It is, therefore, suggested thatGhMYBantiV possibly plays an important role in biotic andabiotic stress response in cotton.